2006
DOI: 10.1002/jat.1201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphodiesterase (PDE) inhibitors on human ether‐a‐go‐go related gene (hERG) channel activity

Abstract: It is presumed that phosphodiesterase (PDE) inhibitors have two mechanisms for inhibition of hERG currents in the acute applications to cells: direct channel block, and downregulation of human ether-a-go-go related gene (hERG) activities by PKA-dependent pathway mediated phosphorylation through their inhibitory effects against PDE enzymes. However, it is unknown whether PDE inhibition contributes to the inhibitory effects of PDE inhibitors on hERG currents. This study examined the effects of various PDE inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The same problem can be seen with the vinpocetine molecule. An IC 50 of 32 nm was considered in our study, whereas recently an IC 50 of 130 nm was reported . Clearly, the introduction of uncertainty in the biological activity reduces the performance of the model, and we expected to get a poor predictive model with weak correlation between GRIND descriptors and the activity.…”
Section: Resultsmentioning
confidence: 94%
“…The same problem can be seen with the vinpocetine molecule. An IC 50 of 32 nm was considered in our study, whereas recently an IC 50 of 130 nm was reported . Clearly, the introduction of uncertainty in the biological activity reduces the performance of the model, and we expected to get a poor predictive model with weak correlation between GRIND descriptors and the activity.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, PDE5 inhibitors have already been reported to have a concentration-dependent inhibitory effect on Ikr and prolongation of cardiac repolarization 29 . Interestingly, most PDE inhibitors decreases hERG current directly or indirectly while two PDE3 inhibitors (amrinone and milrinone) fail to exhibit any hERG inhibitory effects 30 . In this study, amrinone did not inhibit Ikr current in the control and HF myocytes, consistent with previous reports 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most PDE inhibitors decreases hERG current directly or indirectly while two PDE3 inhibitors (amrinone and milrinone) fail to exhibit any hERG inhibitory effects 30 . In this study, amrinone did not inhibit Ikr current in the control and HF myocytes, consistent with previous reports 30 . However, our studies further showed that Ikr currents were inhibited by salbutamol after pretreatment with PDE3 inhibitor, and APD was prolonged more.…”
Section: Discussionmentioning
confidence: 99%
“…PPB are either from published data (plain text) or measured in our laboratories (bold italics). [22]; c: [23]; d: [24,25]; e: [26]; f: [27]; g: [28]; h: [19]; i: [29]; j: [30]; k: [31]; l: [32]; m: [33]; n: [34]; o: [35]; p: [36]; q: [37]; r: [38]; s: [39]; t: [40]; u: [41]; v: [42]; w: [43]; x: [44]; y: [45]; z: [46]; aa: [47]; bb: [48]; cc: [49]; dd: [50]; ee: [51]; ff: [52]; gg: [53]; hh: [54]; ii: [55]; jj: [56]; kk: [57]; ll: [58]; mm: [59]; nn: [60]; oo: [61]; pp: [62]; qq: [63]; rr: [64]; ss: [65]; tt: [66]; uu: [67]; vv: [68]; ww: …”
Section: Drugs With a Cardiovascular Target Without A Direct Role In mentioning
confidence: 99%